Positivisme dan Strukturalisme: Sebuah Perbandingan Epistemologi dalam Ilmu Sosial - Galeh Prabowo (JSW (Jurnal Sosiologi Walisongo), 2017)
The emergence of various types in epistemology shows that social sciences has grown dynamically. Several epistemologies which is usually applied by social scientist  such as positivism, historicism, materialism, phenomenology, structuralism, and hermeneutics. Epistemology can be intrepeted as a philosophical view that used in assessing social and cultural phenomena. As a social researcher, we have to be aware for using an epistemology  in order to get results on the right path. In the other hand, most of the epistemologies have the advantages and weakness for understanding social and cultural phenomena. Therefore, this paper aim to explain the comparison between positivism and structuralism. It will be analyzed through some elements in epistemology for instance basic assumption, model and value.